2017
DOI: 10.1175/jcli-d-15-0614.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Generation of Lorenz’s Available Potential Energy in a Global Climate Model

Abstract: Previous studies have estimated global available potential energy (APE) and global APE generation, but no study has focused on the geographic distribution of contributions to global APE and APE generation. To obtain the information needed for this analysis, simulations were performed using the NCAR CESM1.0.4 climate model. Based on these simulation results, maps of the spatial and seasonal distribution of APE contributions and APE generation in the atmosphere were obtained from the analysis. APE is generated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Near-surface KE is generated because of either near-surface pressure gradients or the downgradient transport of KE along wind speed gradients from the upper levels of the atmosphere. Both of these sources are ultimately driven by gradients in diabatic heating ( 8 ). In this manner, the energy cycle within the atmosphere imposes a limit on electricity generation by wind turbines, which acts at the scale of kinetic energy extraction (KEE) rates required to meet the primary power generation demands of the 21 st century.…”
mentioning
confidence: 99%
“…Near-surface KE is generated because of either near-surface pressure gradients or the downgradient transport of KE along wind speed gradients from the upper levels of the atmosphere. Both of these sources are ultimately driven by gradients in diabatic heating ( 8 ). In this manner, the energy cycle within the atmosphere imposes a limit on electricity generation by wind turbines, which acts at the scale of kinetic energy extraction (KEE) rates required to meet the primary power generation demands of the 21 st century.…”
mentioning
confidence: 99%
“…Basic theory suggests that decreased equator-topole temperature differences should decrease wind speeds overall. Indeed, one idealized study (14) concluded that the generation and dissipation of atmospheric kinetic energy would decrease by ∼10% in a world with quadrupled atmospheric carbon dioxide. However, how this plays out in the utility of wind power production is yet to be determined.…”
Section: Carbon Intensity Of Energymentioning
confidence: 99%
“…2 (e.g., Li et al 2007) or Eq. 1 (e.g., Ahbe and Caldeira 2017). Although these approaches appear to yield plausible results, it goes without saying that it would be far more satisfactory to base such analyses directly from a truly local definition of APE.…”
Section: Introductionmentioning
confidence: 99%